International Day Program as a Medium for English Skill Development in Students’ Perceptions - Iffadah, Amelia Resti; Tasyani, Fibra Aura; Rifa'i, Cep Ahmad; Putri, Ida Masayu (Universitas Teknokrat Indonesia, 2024)
English has become one of the most important languages in the world. This makes English a competency that is very necessary in today’s global work or educational institutions. However, many of us have limited access to learning and developing our English language skills. Therefore, this paper aims to find out the perceptions of students at one of the Islamic universities in East Java, which requires students to stay at a university boarding school that has an International Day program as a medium for developing students’ English skills which it is also aimed to be the requirements for the students graduation from the university boarding school. To achieve the objectives of this research, interview analysis was used to describe their perceptions regarding the implementation of the program. This research also used a qualitative approach with direct interviews with 5 students from different educational backgrounds. The results of this research figured out that some students only regarded the International Day program as a form of formality for the university boarding school graduation. However, there are also those who use this program as a murajaah for their previous English language skills and as a medium for developing English language skills. Apart from that, this research also highlights the existence of a gap between students’ expectations and reality regarding the implementation of the International Day program, and it was found that there is a quite big gap regarding this. So, it is necessary to evaluate the implementation of the program in terms of intensity, rules, and supervision, as well as additional support for each student, so that students can be more active in carrying out the program. Overall, this research provides insight into the students’ perceptions of English language skills development programs and emphasizes the importance of aligning program implementation with the students’ expectations for better future outcomes.